Incentivo de la actividad física mediante el uso de los contadores de pasos en pacientes con EPOC - Mendoza I., Laura (Revista Hospital Clínico Universidad de Chile, 2010)
The Chronic Obstructive Pulmonary Disease (COPD) is the main respiratory chronic condition, which mortality and disability are increasing. The main symptoms of COPD patients are dyspnoea and exercise intolerance, that reduce the physical activity levels of patients and generate a vicious circle that increases the exercise intolerance and deteriorates their quality of life. The pulmonary rehabilitation programs (PR) have demonstrated a clear effect improving exercise tolerance, reducing dyspnoea and improving health related quality of life in COPD patients. However, PR programs are very difficult to implement because require a multi professionalteam, a special physical environment and they are very expensive. In fact, in Chile a very low proportion of patients suffering COPD have the opportunity to participate in a PR program. It has been demonstrated that pedometers are effective to increase the level of physical activity in elderly subjects and in others medical conditions like diabetes and hypertension associated with health’s benefits. However, the effectiveness as incentive of physical activity of pedometers is not still demonstrated in COPD patients. If the pedometers are useful as incentive of physical activity associated with health’s benefit in COPD patients, we can have a new alternative toimprove the quality of life of COPD patients that also could be incorporated as recommendation in the public health’s guidelines.